Design and Development of IoT-Based Automated Attendance System Using Facial Recognition - Makigod, George Michael G. (2024)
The IoT Based Automated Attendance System was designed and developed to make an efficient contactless attendance marking system with a mobile application feature. This study aimed to improve the traditional attendance log system and contact fingerprint attendance within an institution through the use of facial recognition. The study used the OpenCV and Python Programming in order to create the facial recognition program, while the mobile application was developed through the use of Visual Studio Code and Android Studio. The prototype was composed of mini pc which handled all the processes the device had to execute. The computer was used to interface other components of the device such as webcam, monitor, keyboard, and mouse. Since this is an automated attendance system, portability and efficiency were given importance. The prototype’s performance was tested and monitored through the use of 100 participants including the researchers themselves. The project was tested by the Department of Computer, Electronics, and Electrical Engineering (DCEE) at the Engineering Science Building, Cavite State University, Indang, Cavite with the Electronics Engineer Professors. Based on the results of the evaluation, the design project succeeded in achieving its objectives. The overall performance was considered satisfactory. The cost computation of the system amounted to PHP 14,150.00.